2009
DOI: 10.1007/s10484-009-9110-5
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Anxiety Correlate Differently with Salivary Free Cortisol in the Morning in Patients with Functional Somatic Syndrome

Abstract: Patients presenting with functional somatic syndrome (FSS) are common, and the symptoms are persistent and difficult to treat for doctors and costly for society. The aim of this study was to clarify the common pathophysiology of FSS, especially the relationship between hypothalamic-pituitary-adrenal (HPA) axis function and psychological characteristics of patients with FSS. The subjects were 45 patients with FSS and 29 healthy controls. Salivary free cortisol was measured in the morning, and psychological test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
0
7
0
3
Order By: Relevance
“…For example, in IBS which exhibits a high degree of comorbidity with depression and anxiety disorders, 5,6 lowered secretion of ACTH and cortisol to a CRH challenge, lowered evening saliva cortisol and a lowered level of daytime ACTH secretion have been described. [9][10][11] Patients with functional somatic syndromes show negative correlations between morning saliva cortisol and depressive symptoms 48,49 and patients with major depression show a negative correlation between cortisol and somatoform dissociation. 50 Depressed patients with a comorbid somatoform disorder show an attenuated HPA-axis response to a combined dexamethasone/CRH test.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in IBS which exhibits a high degree of comorbidity with depression and anxiety disorders, 5,6 lowered secretion of ACTH and cortisol to a CRH challenge, lowered evening saliva cortisol and a lowered level of daytime ACTH secretion have been described. [9][10][11] Patients with functional somatic syndromes show negative correlations between morning saliva cortisol and depressive symptoms 48,49 and patients with major depression show a negative correlation between cortisol and somatoform dissociation. 50 Depressed patients with a comorbid somatoform disorder show an attenuated HPA-axis response to a combined dexamethasone/CRH test.…”
Section: Discussionmentioning
confidence: 99%
“…Results suggested attenuated pituitary and adrenocortical activity in the patient group who had lower salivary cortisol levels and a less robust response to CRH. 179 In a study by Mutsuura et al , 180 a relationship between HPA axis function and mood was reported in FD and other functional syndromes (patients had a diagnosis of either FD, IBS, chronic tension headaches, CFS, chronic pain, or other functional GI disorder) compared to healthy controls. In the patient group, there was a negative correlation with depressive mood and morning free salivary cortisol although a positive correlation was observed in healthy controls.…”
Section: Proposed Pathophysiologic Mechanismsmentioning
confidence: 99%
“…In the patient group, there was a negative correlation with depressive mood and morning free salivary cortisol although a positive correlation was observed in healthy controls. 180 Although these studies showed some evidence of HPA axis dysregulation in FD patients, limitations included combining FD with other functional syndrome, differences in medications used by these patients, and underlying comorbid depression/ anxiety/or stress state, which may affect cortisol levels.…”
Section: Neuroendocrine Dysregulationmentioning
confidence: 99%
“…In our hands, the intra-assay and interassay CV were <6%. Low saliva F concentrations have been associated with chronic stress, burnout, fibromyalgia, and depression (14)(15)(16). Therefore, we chose low saliva F concentrations as an indicator of chronic stress.…”
Section: F Analysismentioning
confidence: 99%